Foreign language didactic : Teaching and Learning (مجلة إحالات, 2026)
This communication is a contribution to research in the field of foreign language didactics, il focuses on the teaching and learning strategies adopted in the education system, where the teacher has passed to an accompanist as well as the pupil has become the center of the educational process. Currently, research in the didactic field remains a scientific and methodological necessity. Because of the evolution of the sector, the rehabilitation of the education system, in particular the methods ofteaching/learning in language classes, should be taken into account. This work aims to shed light onthe main strategies for teaching / learning a language in order to achieve the educational purpose.